2011
DOI: 10.1364/oe.19.00b415
|View full text |Cite
|
Sign up to set email alerts
|

40nm wavelength tunable gain-switched optical comb source

Abstract: A wavelength tunable optical comb is generated based on the gain-switching of an externally seeded Fabry-Pérot laser diode. The comb consists of about eight clearly resolved 10 GHz coherent sidebands within 3 dB spectral envelope peak and is tunable over the entire C-band (1530 to 1570 nm). The optical linewidth of the individual comb tones is measured to be lower than 100 kHz, and the RIN of the individually filtered comb tones (<-120 dB/Hz) is shown to be comparable to the entire unfiltered comb (<-135 dB/Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…However, it needs the optical power beyond 50 W prior to HNLF. Another typical scheme of broadband OFC generation is mainly based on electro-optical modulation, which can be found in [9][10][11][12][13]. In [10], a wavelength tuning range is improved to 40 nm, but the comb lines are not simultaneous and seamless.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it needs the optical power beyond 50 W prior to HNLF. Another typical scheme of broadband OFC generation is mainly based on electro-optical modulation, which can be found in [9][10][11][12][13]. In [10], a wavelength tuning range is improved to 40 nm, but the comb lines are not simultaneous and seamless.…”
Section: Introductionmentioning
confidence: 99%
“…Another typical scheme of broadband OFC generation is mainly based on electro-optical modulation, which can be found in [9][10][11][12][13]. In [10], a wavelength tuning range is improved to 40 nm, but the comb lines are not simultaneous and seamless. In [12], although an OFC with a bandwidth of 10 nm is obtained using a dual-driven Mach-Zehnder modulator (DD-MZM), feedback loops and high quality optical filters are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of this approach lies in its suitability for monolithic integration as well as the flexible tunability in both channel spacing and central wavelength 2,3 . Moreover, it has been shown that external injection effectively transfers the narrow emission linewidth of the injection master to the slave comb lines 2,3 , making such a comb source particularly attractive for coherent applications requiring low linewidth sources.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an external cavity laser (ECL) with a linewidth of ∼200 kHz and an output power of 6 dBm was used to inject into the gain switched DFB laser. The external injection from a single low linewidth ECL ensures the transfer of the low linewidth (master) to each of the gain-switched DFB laser (slave) comb tones [10], thereby enabling them to be employed as carriers for advanced modulation format data signals especially at low baud rates (where the linewidth requirement is more stringent). The gain-switched comb source, as illustrated in Fig.…”
mentioning
confidence: 99%